If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying N + 14 = 3N + -8 Reorder the terms: 14 + N = 3N + -8 Reorder the terms: 14 + N = -8 + 3N Solving 14 + N = -8 + 3N Solving for variable 'N'. Move all terms containing N to the left, all other terms to the right. Add '-3N' to each side of the equation. 14 + N + -3N = -8 + 3N + -3N Combine like terms: N + -3N = -2N 14 + -2N = -8 + 3N + -3N Combine like terms: 3N + -3N = 0 14 + -2N = -8 + 0 14 + -2N = -8 Add '-14' to each side of the equation. 14 + -14 + -2N = -8 + -14 Combine like terms: 14 + -14 = 0 0 + -2N = -8 + -14 -2N = -8 + -14 Combine like terms: -8 + -14 = -22 -2N = -22 Divide each side by '-2'. N = 11 Simplifying N = 11
| 15r^2-44r+120=-30+11r | | z^6-11=0 | | 19+7=56 | | xdy+(x^2-3y)dx=0 | | -69x=85x-22 | | 3x-6+2x-6=10x-8 | | -3x^2+8x+14=0 | | -14=2+4w | | 2(x-7)-6=-2(-7x+1)-4x | | 1.6x+x=130 | | 2x+14(x+1)=0 | | -110=-8z+2 | | -7(n+2)+16=-4n-4 | | 2x+14-(x-1)=0 | | 2*(x+i*y)=6-i*3 | | -4+y=41 | | 33-19=2(x-8) | | 6x-36+2=8x-8 | | 4x+15=16x-11 | | -2x^2-9x+14=0 | | 2x^2-x-6=y | | 6x+4=-2x-7 | | 6(5-X)=-2(X+43) | | 50m+42975=45450-175m | | b+25=-69 | | 2=5y+2 | | y-3=3/4(x-16) | | y/10=3/6 | | 6/9=y/12 | | log(8x-15)=2 | | 11x(12-x)-30=20x+59-6x(4x-13) | | 1/6+2/3+1/18=n |